A extensão universitária como estratégia para o desenvolvimento regional: o caso da Universidade Federal da Fronteira Sul - Campus Cerro Largo - Frota, Mariângela Brum (2017)
The University Extension is an educational process, cultural and scientific process that, inseparably, articulates teaching and research, constituting a potentially important space for the achievement of the practice and mutual exchange of knowledge between academy and society, in addition to being an instrument of academic and professional training. Characterized as an activity of social relevance, constantly receives the stigma of being inferiorized before all other functions of the academic making. From this perspective, this dissertation aims to analyze the experience of University Extension of Federal University of Fronteira Sul - Campus Cerro Largo, in the period from 2010 to 2016, identifying the practices, the possibilities and the limits of its contribution to sustainable regional development. With regard to methodological aspects, the research, as to the approach, is qualitative, classifying, according to their nature, as applied. From the point of view of the goals is descriptive, outlined by the study of simple case. With respect to technical procedures is bibliographic, documental and field. The survey was conducted in the UFFS - Campus Cerro Largo. For data collection we used the technique of structured interview, applied to managers of the institution, coordinators and participants of extension programs/projects. The analysis and interpretation of data was operationalized by content analysis, from five categories defined in advance. The results show that the University Extension promotes regional development, as it promotes the approximation of the university with society, and manages to make the academy with respect to regional demands, articulating the teaching and research in order to enhance academic and professional training. The limits of this activity are related to restrictions on operating order, ideological and budget. Despite these limiting issues, the University Extension in UFFS has advanced and is an area of social participation, visibility and credibility of academic activities. The University Extension promotes regional development, as it promotes the approximation of the university with society, and manages to make the academy with respect to regional demands, articulating the teaching and research in order to enhance the academic and professional.